Perinatal outcomes among pregnant women living with HIV initiating antiretroviral therapy preconception and antenatally: systematic review and meta-analysis - Boering, P; Murray, C; Portwood, C; Hey, M; Thompson, L; Beck, K; Cowdell, I; Sexton, H; Kumarendran, M; Brandon, Z; Kirtley, S; Hemelaar, J (Lippincott, Williams & Wilkins, 2025)
Objective: Increasingly, pregnant women living with HIV (WLHIV) initiate antiretroviral therapy (ART) before conception. We assessed the risk of adverse perinatal outcomes among pregnant WLHIV initiating ART preconception or antenatally, compared with women without HIV or ART-naïve WLHIV. Design: Systematic review and meta-analysis Methods: We searched PubMed, EMBASE, CINAHL, and Global Health for studies published between 1/1/1980 and 14/7/2023. We assessed the association of preconception/antenatal ART initiation with preterm birth (PTB), very PTB (VPTB), spontaneous PTB (sPTB), low birthweight (LBW), very LBW (VLBW), small-for-gestational-age (SGA), very SGA (VSGA), stillbirth and neonatal death (NND). Data were analysed using random effects meta-analyses. Quality assessments, subgroup and sensitivity analyses were conducted. PROSPERO registration: CRD42021248987. Results: Thirty-one cohort studies were eligible, including 199,156 women in 19 countries. WLHIV with preconception ART were associated with increased risk of PTB (risk ratio 1.55; 95%CI 1.27–1.90), VPTB (2.14,1.02–4.47), LBW (2.19, 1.32–3.63), VLBW (3.34, 1.08–10.35), SGA (1.92, 1.01–3.66), and VSGA (2.79, 1.04–7.47), compared with women without HIV. WLHIV with antenatal ART were associated with increased risk of PTB (1.35, 1.15–1.58), LBW (2.16, 1.39–3.34), VLBW (1.97, 1.01–3.84), SGA (1.77, 1.10–2.84), and VSGA (1.21, 1.09–1.33), compared with women without HIV. Compared to ART-naïve WLHIV, WLHIV with preconception or antenatal ART were associated with increased risk of SGA (preconception: 1.40, 1.12–1.73; antenatal: 1.39, 1.11–1.74) and VSGA (preconception: 2.44, 1.63–3.66; antenatal: 2.24, 1.48–3.40). Conclusion: Among WLHIV, both preconception and antenatal initiation of ART are associated with increased risks of adverse perinatal outcomes, compared to women without HIV and ART-naïve WLHIV.